Impact of drinking water quality on the occurrence of and the development of dental diseases in seafarers of overseas navigation - Plotiansky, I. V.; Stets, N. V.; Badiuk, N. S. (Journal of Education, Health and Sport, 2018)
The quality of the water consumed by the crew members of sea-going vessels on the voyages depends on many factors, in particular, on the quality of the initial water supplied on the vessel, its change during the transfer / transportation, the condition of the elements of the ship’s water supply system (the water-supply network, water tanks, their anticorrosion coatings), methods of conditioning water on long-haul flights. Consumption of high-quality drinking water in sufficient quantity can optimize the well-being and performance of crew members, especially those who perform flights and physical work in difficult climatic and geographical conditions. The quality of drinking water affects the condition of your teeth. The main goal of the prevention of dental diseases is to eliminate the causes of their occurrence and development, as well as to create conditions for increasing the resistance of the seamen’s organism to changing the composition of drinking water. The article presents the data of the dental clinic examinations of the Odessa Basin Dental Clinic with a work experience of more than 30 years and were on flights up to 10 years on ships.